2015
DOI: 10.1063/1.4926604
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bolometric properties of TiO2−x thin films by thermal annealing

Abstract: The effect of thermal annealing on the bolometric properties of TiO2−x films was investigated. The test-patterned TiO2−x samples were annealed at 300 °C temperature in order to enhance their structural and electrical properties for effective infrared image sensor device applications. The crystallinity was changed from amorphous to rutile/anatase in annealed TiO2−x films. Compared to the as-deposited samples, a decrement of the band gap and a decrease of the electrical resistivity were perceived in annealed sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Consequently, the resistivity and temperature coefficient of resistance of titanium oxide films can be changed by many orders of magnitude by varying the deposition and annealing parameters. [13][14][15] There are numerous methods including sol-gel process, chemical vapor deposition, thermal evaporation, and reactive magnetron sputtering that can be used to prepare titanium oxide films. However, there are quite few TCR characterization of TiO x films which are mostly deposited by RF reactive magnetron sputtering as well as DC sputtering.…”
Section: Tcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the resistivity and temperature coefficient of resistance of titanium oxide films can be changed by many orders of magnitude by varying the deposition and annealing parameters. [13][14][15] There are numerous methods including sol-gel process, chemical vapor deposition, thermal evaporation, and reactive magnetron sputtering that can be used to prepare titanium oxide films. However, there are quite few TCR characterization of TiO x films which are mostly deposited by RF reactive magnetron sputtering as well as DC sputtering.…”
Section: Tcrmentioning
confidence: 99%
“…Kwon et al 16 investigated reactively sputtered TiO x films and obtained TCR value up to 2.8%/K. Reddy et al, 14,17 with the same deposition technique but different oxygen content, obtained the TCR value up to 3.66%/K. TiO x films prepared by Jiang et al 13 via reactive DC sputtering showed a TCR value of 3.3%/K.…”
Section: Tcrmentioning
confidence: 99%
“…Most importantly, these schemes led to low bolometric noise in these Ti oxide systems. 110,111 Among all the semiconducting materials, vanadium oxide (VO x ) emerged to be the most promising candidate for IR BM, because of its high RT-TCR (in the range from ∼2%/K to ∼5%/ K), low 1/f noise, high IR absorption, and tunable resistivity. Pulsed DC sputtering and pulsed laser deposition techniques are widely used for the deposition of VO x thin films.…”
Section: { }mentioning
confidence: 99%
“…For instance, doping Nb led to an increase in the TCR value with a simultaneous reduction in the electrical resistivity. Most importantly, these schemes led to low bolometric noise in these Ti oxide systems. , …”
mentioning
confidence: 98%
“…For that reason, we focused on TiO 2−x as an alternative heat-sensitive material, as great progress has been made in the areas of device fabrication and improvements of bolometric properties [12][13][14]. Conversely, TiO 2−x materials are highly sensitive to oxygen, and it is very difficult to tune the resistivity value during the fabrication process of the samples.…”
Section: Introductionmentioning
confidence: 99%